2019
DOI: 10.1002/jcp.29012
|View full text |Cite
|
Sign up to set email alerts
|

In silico evidence of high frequency of miRNA‐related SNPs in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is the dominant histological type of esophageal cancer significantly reported in developing nations. There is an increasing evidence suggesting that single nucleotide polymorphisms (SNPs) in the untranslated regions of genes (3′-UTRs) targeted by microRNAs (miRNAs) can change the target gene's expression and thereby affect the individual's cancer risk. Thus, in support of the role of SNPs occurring in miRNA target sites (miR-TS-SNPs) in the cancer, we analyzed the next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Genetic variants, specifically the single nucleotide polymorphisms (SNPs), located in lncRNAs genes have the potential to make a crucial impact on lncRNA expression levels, processing or on the secondary structure of lncRNAs, which results in cancer development and progression as well as the alteration of drug responses. [131][132][133][134] Dysregulation in lncRNAs expression profile has been demonstrated with high throughput analysis in many tumor cells. [135][136][137] For instance, H19…”
Section: Lncrna Polymorphism In Crcmentioning
confidence: 99%
“…Genetic variants, specifically the single nucleotide polymorphisms (SNPs), located in lncRNAs genes have the potential to make a crucial impact on lncRNA expression levels, processing or on the secondary structure of lncRNAs, which results in cancer development and progression as well as the alteration of drug responses. [131][132][133][134] Dysregulation in lncRNAs expression profile has been demonstrated with high throughput analysis in many tumor cells. [135][136][137] For instance, H19…”
Section: Lncrna Polymorphism In Crcmentioning
confidence: 99%
“…Recently, a large body of investigations reported diverse roles of non-coding RNA, particularly long non-coding RNA (lncRNA), in biological processes of different sorts of cancer [ 11 13 ]. LncRNAs are a group of non-coding RNAs with more than 200 nt in length and with no or little capability of coding proteins [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data demonstrated that the lncRNA WDFY3-AS2, AC108449.2,DLEU2, AC007128.1,and AP003356.1 as potential diagnostic and prognostic biomarker in the ESCApatients (Figure6).Esophageal cancer is one of the most aggressive types of cancer with an increasing rate of death and dismal prognosis. Previous investigations highlighted non-coding RNA particularly lncRNA's roles in cancer development, progression, and clinicopathological features of the patients(13)(14)(15). A large body of studies considered lncRNAs as a major contributor to ESCA development and showed the lncRNAs prognosticand diagnostic values for the ESCA patients (16).…”
mentioning
confidence: 99%